2016
DOI: 10.1186/s12918-016-0347-3
|View full text |Cite
|
Sign up to set email alerts
|

In silico metabolic network analysis of Arabidopsis leaves

Abstract: Background: During the last decades, we face an increasing interest in superior plants to supply growing demands for human and animal nutrition and for the developing bio-based economy. Presently, our limited understanding of their metabolism and its regulation hampers the targeted development of desired plant phenotypes. In this regard, systems biology, in particular the integration of metabolic and regulatory networks, is promising to broaden our knowledge and to further explore the biotechnological potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 112 publications
(132 reference statements)
0
23
0
Order By: Relevance
“…For Arabidopsis , we adopted the previously published and extensively used leaf‐specific metabolic model AraGEM (Gomes de Oliveira Dal’Molin et al , 2015; de Oliveira Dal’Molin et al , 2010) and altered 50 reaction directions so as to remove thermodynamically infeasible cycles (Table S4). AraGEM captured more metabolites present in the metabolomics dataset than the more recently published model (Beckers et al , 2016) thereby enabling us to better constrain the feasible solution space using reaction rate expressions derived from mass‐action kinetics. The Arabidopsis GSM constructed by (Mintz‐Oron et al , 2012) had a greater number of reactions participating in thermodynamically infeasible cycles.…”
Section: Genome‐scale Metabolic Model Reconstructionmentioning
confidence: 99%
“…For Arabidopsis , we adopted the previously published and extensively used leaf‐specific metabolic model AraGEM (Gomes de Oliveira Dal’Molin et al , 2015; de Oliveira Dal’Molin et al , 2010) and altered 50 reaction directions so as to remove thermodynamically infeasible cycles (Table S4). AraGEM captured more metabolites present in the metabolomics dataset than the more recently published model (Beckers et al , 2016) thereby enabling us to better constrain the feasible solution space using reaction rate expressions derived from mass‐action kinetics. The Arabidopsis GSM constructed by (Mintz‐Oron et al , 2012) had a greater number of reactions participating in thermodynamically infeasible cycles.…”
Section: Genome‐scale Metabolic Model Reconstructionmentioning
confidence: 99%
“…First, as outlined in Supplementary Figure 1, the network was reconstructed based on biochemical reactions derived from the genomebased pathway of carbon metabolism in cassava, MeRecon (Siriwat, 2012). Next, the 129 biochemical reactions (Figure 1) common in the rice (Lakshmanan et al, 2015;Lakshmanan et al, 2013) and Arabidopsis leaf models (Beckers et al, 2016;de Oliveira Dal'Molin et al, 2010a;Mintz-Oron et al, 2012;Saha, et al, 2011) were added, to reflect the metabolism in photosynthetic tissues. Additionally, 47 reactions overlapping two of the leaf models, at least, were added to fully connect the common reactions to MeRecon.…”
Section: A Qualitative Model Of Carbon Metabolism In Cassava Leavesmentioning
confidence: 99%
“…To date, over 50 genome-scale metabolic models have been constructed in a broad range of organisms, from simple prokaryotes to complex eukaryotes (Kim et al, 2012). However, due to the following difficulties: (i) lack of complete genome information, (ii) insufficient knowledge about the metabolic network and missing components, (iii) duplication of metabolic pathways and transport of metabolites across compartments, (iv) metabolic differences at cell and tissue levels, and varied metabolic response to environmental change, only a few exist for plants, such as Arabidopsis (Beckers et al, 2016;de Oliveira Dal'Molin et al, 2010a;Mintz-Oron et al, 2012), maize (Zea mays) (de Oliveira Dal'Molin et al, 2010b;Saha et al, 2011), and rice (Oryza sativa) (Lakshmanan et al, 2015;Lakshmanan et al, 2013). Metabolic modeling has been employed to study metabolic adaptation to abiotic stress (Lakshmanan et al, 2016;Lakshmanan et al, 2013) and yield improvement in plants, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic Control Analysis (MCA) (Kacser and Burns, 1973;Moreno-Sánchez et al, 2008), which is used to quantify the amount of control a specific step exerts on a pathway, has shown that the control of oil accumulation in seeds occurs both through FA synthesis (e.g., the FA synthase complex) and through triacylglyceride (TAG) assembly (Ramli et al, 2002). Combined network analysis for prediction of metabolic pathways based on metabolomics data, in silico analysis and machine learning was recently conducted in tomato, displaying the potential of artificial intelligence in model simulation of metabolic networks (Beckers et al, 2016;de Luis Balaguer and Sozzani, 2017;Toubiana et al, 2019). However, these modeling efforts are either limited to steady-state conditions or conducted in the context of a single pathway.…”
Section: Introductionmentioning
confidence: 99%